2005
DOI: 10.4161/auto.1.3.2068
|View full text |Cite
|
Sign up to set email alerts
|

Sera from patients with type 2 Diabetes and Neuropathy Induce Autophagy and Colocalization with Mitochondria in SY5Y cells

Abstract: The etiology of diabetic neuropathy is multifactorial and not fully elucidated, although oxidative stress and mitochondrial dysfunction are major factors. We reported previously that complement-inactivated sera from type 2 diabetic patients with neuropathy induce apoptosis in cultured neuronal cells, possibly through an autoimmune immunoglobulinmediated pathway. Recent evidence supports an emerging role for autophagy in a variety of diseases. Here we report that exposure of human neuroblastoma SH-SY5Y cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 32 publications
6
58
0
Order By: Relevance
“…Towns et al (2005) found that serum factors, likely autoantibodies, purified from patients with SLE were able to induce autophagy in neuroblastoma cell lines, providing a further link between autophagy and SLE. Accordingly, several other groups have reported the activated autophagy pathway in T and B lymphocytes as a mechanism for survival of autoreactive T and B lymphocytes.…”
mentioning
confidence: 83%
“…Towns et al (2005) found that serum factors, likely autoantibodies, purified from patients with SLE were able to induce autophagy in neuroblastoma cell lines, providing a further link between autophagy and SLE. Accordingly, several other groups have reported the activated autophagy pathway in T and B lymphocytes as a mechanism for survival of autoreactive T and B lymphocytes.…”
mentioning
confidence: 83%
“…Similar autophagy activation was also observed in SH-SY5Y neurons treated by sera from active lupus patients. 133 These data might allow the hypothesis that autoimmune diseases correlate with unbalanced autophagy. But, to date, no clear link and precise mechanisms have been resolved with regard to autoantibodies from classical autoimmune disease in mediating autophagy.…”
Section: Autophagy In Antigen Processing and Presentationmentioning
confidence: 99%
“…For example, sera from type 2 diabetic patients with neuropathy or a subpopulation of patients with neurogenic chronic intestinal pseudo-obstruction, [133][134][135][136][137] are associated with increased levels of autophagosomes involving the FAS receptor complex. Similar autophagy activation was also observed in SH-SY5Y neurons treated by sera from active lupus patients.…”
Section: Autophagy In Antigen Processing and Presentationmentioning
confidence: 99%
“…Each patient's serum was screened for its ability to induce autophagy using the vital lipophilic dye monodansyl cadaverine (MDC) which non-specifically labels intracellular vacuoles including autophagosomes as described previously. 28 The subpopulation of CIP sera that stimulated autophagy via autoantibody-mediated activation of a Fas-dependent pathway was designated CIP with aNA. All the sera screened for their ability to induce autophagy using the MDC and anti-LC3 immunofluorescence assays were complement-inactivated (heated in a water bath at 56°C for 40 min).…”
Section: Inclusion Criteria and Patientsmentioning
confidence: 99%
“…28 The cells were subsequently exposed to the primary anti-LC3 antiserum (kindly provided by Dr. Tamotsu Yoshimori, Department of Cell Biology, National Institute for Basic Biology, Okazaki, Japan) at 1:400 dilution, anti-mitochondrial antibody (AMA) at 1:100 dilution (Chemicon International, Temecula, CA), anti-Fas activated death domain (FADD) antibody at 1:100 dilution (Cell Signaling, Tropix, Bedford MA) and secondary antibodies (Alexa Fluor 495, goat anti-rabbit IgG, 1:400, and Alexa Fluor 488, goat anti-mouse IgG, 1:400, Molecular Probes, Eugene, OR) depending on the donor species of the primary antibody, in blocking buffer for 2 h at room temperature. For the detection of IgG, the antibody utilized was goat anti-human IgG-Fc, HRP-conjugated (1:3000).…”
Section: Inclusion Criteria and Patientsmentioning
confidence: 99%